A novel methylation derivatization method for δ18O analysis of individual carbohydrates by gas chromatography/pyrolysis–isotope ratio mass spectrometry. (11th December 2015) - Lehmann, Marco M.; Fischer, Maria; Blees, Jan; Zech, Michael; Siegwolf, Rolf T. W.; Saurer, Matthias
Abstract : Rationale: The oxygen isotope ratio (δ 18 O) of carbohydrates derived from animals, plants, sediments, and soils provides important information about biochemical and physiological processes, past environmental conditions, and geographical origins, which are otherwise not available. Nowadays, δ 18 O analyses are often performed on carbohydrate bulk material, while compound‐specific δ 18 O analyses remain challenging and methods for a wide range of individual carbohydrates are rare. Methods: To improve the δ 18 O analysis of individual carbohydrates by gas chromatography/pyrolysis–isotope ratio mass spectrometry (GC/Pyr‐IRMS) we developed a new methylation derivatization method. Carbohydrates were fully methylated within 24 h in an easy‐to‐handle one‐pot reaction in acetonitrile, using silver oxide as proton acceptor, methyl iodide as methyl group carrier, and dimethyl sulfide as catalyst. Results: The precision of the method ranged between 0.12 and 1.09‰ for the δ 18 O values of various individual carbohydrates of different classes (mono‐, di‐, and trisaccharides, alditols), with an accuracy of a similar order of magnitude, despite high variation in peak areas. Based on the δ 18 O values of the main isomers, important monosaccharides such as glucose and fructose could also be precisely analyzed for the first time. We tested the method on standard mixtures, honey samples, and leaf carbohydrates extracted from Pinus sylvestris, showing that the method is also applicable to different carbohydrate mixtures. Conclusions: The new methylation method shows unrivalled accuracy and precision for δ 18 O analysis of various individual carbohydrates; it is fast and easy‐to‐handle, and may therefore find wide‐spread application. Copyright © 2015 John Wiley & Sons, Ltd.